2018
DOI: 10.1590/1807-7692bar2018170055
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sentiment and Risk in Financial Markets

Abstract: This article estimates association coefficients between measures of market sentiment and risk in the U.S., German and Chinese markets. In terms of risk, four measures were considered: standard deviation, value at risk, expected shortfall and shortfall deviation risk. For market sentiment, data was collected using the Psych Signal technology, which is based on the behavior of investors on social networks. The results indicate significant statistical associations, with the direction of association having financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
5
0
3
Order By: Relevance
“…In their empirical study, Paraboni et al (2018) found an association between market sentiment and risk. This implies that the behavioral aspect of risk management should not be ignored, and the authors recommend that future studies further explore this relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their empirical study, Paraboni et al (2018) found an association between market sentiment and risk. This implies that the behavioral aspect of risk management should not be ignored, and the authors recommend that future studies further explore this relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the access to information and the level of risk taken by the investors, Kaufman e Weber (2013) identified that additional information (complementary information that firms provide) lead to more investor confidence, allowing them to take higher risks in their investments. Paraboni et al (2018) sought to understand the perceptions of liquidity and risk in the American, Chinese and German markets through the assumptions of the Prospect Theory. Their findings indicated that, when there is low perceived liquidity in the market, investors reduce the negotiated volume due to the increase in risk, and that in the opposite scenario, when there is high perceived liquidity, there is an increase in negotiations due to the decrease in risk.…”
Section: Investment Decisionsmentioning
confidence: 99%
“…Em uma análise da relação entre risco e sentimento nos mercados americano, alemão e chinês, Paraboni et al (2018) confirmaram empiricamente que em momentos de baixa liquidez a percepção de risco dos investidores aumenta e por isso eles tendem a reduzir o volume de negociação. Por outro lado, em momentos de alta liquidez, há um aumento no volume de negociação e uma consequente diminuição no risco.…”
Section: Revisão De Literaturaunclassified
“…Consequentemente, e por extensão a esses resultados, é presumível que investidores com confiança insuficiente tenham mais aversão ao risco e diminuam suas negociações quando percebem que o resultado poderá ser negativo (Dhaoui et al 2013). Esse resultado corrobora com o trabalho de Paraboni et al (2018) que já havia encontrado evidências de que em momentos de baixa liquidez a percepção de risco dos investidores aumenta e eles tendem a reduzir o volume de negociação.…”
Section: Variáveisunclassified
See 1 more Smart Citation